Perancangan key risk indicators dalam manajemen risiko - Indriasvary, Cindy Dea; Wijayati, Nureni (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The purpose of this research is to design key risk indicators (KRI) or the main risk indicators for the company’s significant risks. This research takes a case study at PT. A, which operates as a gas energy provider company. The method used in this research is qualitative and quantitative. The KRI design is carried out in the form of determining the medium risk and then determining the root causes, KRI indicators, and the threshold of significant risks that affect the company’s performance both in terms of operational and financial. These significant risks were identified from the company’s risk register. The identified significant risks are the not achieving revenue and the increase in customer receivables. The results of designing KRI from PT. A for not achieving revenue at PT. A obtained three intermediate causes, three root causes, and four KRI indicators. For increase in customer receivables at PT. A obtained one intermediate cause, two root causes, and two KRI indicators. The design of this KRI is expected to provide early mitigation of the potential for major risks that have a major impact on performance achievement.